Dawne i nowe treści w "Modlitwie za Ojczyznę (według ks. Piotra Skargi)" - Okoń, Jan (Tematy i Konteksty, 2014)
Derived from Skarga and properly tied to his name, "Prayer for the Homeland" is today the most famous prayer text of this genre. It is recited publicly, appears on the radio, and even on the Internet. It has fulfilled a special role on Sunday 29th March 1981, at the height of social tension in Poland, just before the general strike announced by Solidarność. At the command of Cardinal Franciszek Macharski it was recited in all the churches of the Archdiocese of Krakow, and the strike was cancelled. John Paul II knew the Prayer and alluded to it. There is no certainty when the prayer came out and who formulated the text, however. The present article aims to answer these questions. "Kazania sejmowe" (“Sejm Sermons”) as the source of the text is indicated. The structure and message of the prayer are presented. Also, a version from 1936 is referred to and recognized as the earliest one in its present form. Also it is proposed that the initiative for the creation of prayer must have been taken by Archbishop Prince Adam Stefan Sapieha as the shepherd of the Archdiocese. The paper also presents extensively the tradition of prayers for the country in the days of the First Republic.